2022
DOI: 10.1088/1755-1315/1120/1/012007
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Rainfall-Runoff in the Diyala River Basin in Iraq using Hydrological Model by HMS with remote sensing, Geo-HMS and ArcGIS

Abstract: In Iraq, the Diyala River (DR) occasionally experiences both droughts and floods. The DR is supplying the amount of water to Tigris River at the south of Baghdad. Estimation of runoff from precipitation is very important because of its impact on decision-making in water resources management. The conceptual and distributed hydrological model was adopted and by HEC-HMS, Geo-HMS, and GIS software, remote digital elevation models were processed. The sensitivity, calibration, and validation were made through the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
0
0
Order By: Relevance
“…Hamdan et al [2021] made a hydrological model of Al-Adhaim River catchment in the northeast of Iraq using the HEC-HMS software and based on the SCS-CN method to estimate the runoff volume, they concluded that the SCS-CN based model was very effective with R 2 equal to 0.9, also they concluded that the CN and the initial abstraction (Ia) were the most sensitive parameters in the model. Alrammahi and Hamdan [2022] made a hydrological model of the Diyala River catchment in Iraq using the HEC-HMS and GIS software, they were doing a sensitivity analysis as well as a calibration and verification for the model through the period of 2017-2021, they get an accuracy of the results of about 95%.…”
Section: Introductionmentioning
confidence: 99%
“…Hamdan et al [2021] made a hydrological model of Al-Adhaim River catchment in the northeast of Iraq using the HEC-HMS software and based on the SCS-CN method to estimate the runoff volume, they concluded that the SCS-CN based model was very effective with R 2 equal to 0.9, also they concluded that the CN and the initial abstraction (Ia) were the most sensitive parameters in the model. Alrammahi and Hamdan [2022] made a hydrological model of the Diyala River catchment in Iraq using the HEC-HMS and GIS software, they were doing a sensitivity analysis as well as a calibration and verification for the model through the period of 2017-2021, they get an accuracy of the results of about 95%.…”
Section: Introductionmentioning
confidence: 99%